An overview of chemosynthetic symbioses in bivalves from the North Atlantic and Mediterranean Sea - Duperron, S. (2018)
Deep-sea bivalves found at hydrothermal vents, cold seeps and organic falls are sustained by chemosynthetic bacteria that ensure part or all of their carbon nutrition. These symbioses are of prime importance for the functioning of the ecosystems. Similar symbioses occur in other bivalve species living in shallow and coastal reduced habitats worldwide. In recent years, several deep-sea species have been investigated from continental margins around Europe, West Africa, eastern Americas, the Gulf of Mexico, and from hydrothermal vents on the Mid-Atlantic Ridge. In parallel, numerous, more easily accessible shallow marine species have been studied. Herein we provide a summary of the current knowledge available on chemosymbiotic bivalves in the area ranging west-to-east from the Gulf of Mexico to the Sea of Marmara, and north-to-south from the Arctic to the Gulf of Guinea. Characteristics of symbioses in 53 species from the area are summarized for each of the five bivalve families documented to harbor chemosynthetic symbionts (Mytilidae, Vesicomyidae, Solemyidae, Thyasiridae and Lucinidae). Comparisons are made between the families, with special emphasis on ecology, life cycle, and connectivity. Chemosynthetic symbioses are a major adaptation to ecosystems and habitats exposed to reducing conditions. However, relatively little is known regarding their diversity and functioning, apart from a few "model species" on which effort has focused over the last 30 yr. In the context of increasing concern about biodiversity and ecosystems, and increasing anthropogenic pressure on oceans, we advocate a better assessment of the diversity of bivalve symbioses in order to evaluate the capacities of these remarkable ecological and evolutionary units to withstand environmental change.